2021
DOI: 10.1080/14760584.2021.1910502
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for herpes zoster vaccination among adults aged 50 years and older in the United States: results from a discrete choice experiment

Abstract: Background: Most adults, and disproportionately fewer African-Americans, have not received herpes zoster (HZ) vaccination despite current recommendations. This study (GSK study identifiers: 208677/HO-17-18066) assessed HZ vaccination preferences among adults aged ≥ 50 years. Research design and methods: In this discrete choice experiment, respondents chose among a 'no vaccine' option and two HZ vaccine profiles, characterized by seven attributes, in a series of choice questions. Random-parameters logit results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
4
5
0
Order By: Relevance
“…In previous studies, respondents have shown a negative preference for vaccine price increases. 32 , 34 , 35 In our study, however, the coefficient of preference for vaccine price is positive, which means that pregnant women are willing to take the vaccine at a higher price (though this relationship was not statistically significant), which is consistent with a previous study of influenza vaccine on the elderly. 36 The reason for this finding may be that pregnant women and the elderly are more concerned about the benefits and risks of vaccination and are relatively insensitive to price, but more research is needed to confirm this.…”
Section: Discussionsupporting
confidence: 88%
“…In previous studies, respondents have shown a negative preference for vaccine price increases. 32 , 34 , 35 In our study, however, the coefficient of preference for vaccine price is positive, which means that pregnant women are willing to take the vaccine at a higher price (though this relationship was not statistically significant), which is consistent with a previous study of influenza vaccine on the elderly. 36 The reason for this finding may be that pregnant women and the elderly are more concerned about the benefits and risks of vaccination and are relatively insensitive to price, but more research is needed to confirm this.…”
Section: Discussionsupporting
confidence: 88%
“…The residents preferred to select HZ vaccine with higher protection rate, longer protection duration, less side-effects and lower prices. This has been confirmed in several previous studies about preferences for HZ vaccination in the US 21 , China 23 and other vaccines' acceptance 28,34,45 . Though The positive or negative signs of most of the coefficients in this study were consistent with our prior hypotheses and thus, showed theoretical validity 28 .…”
Section: Discussionsupporting
confidence: 81%
“…We recruited respondents randomly with acknowledgement after arriving at the health service centers. Eligible respondents were aged ≥ 25 years, living in China, without cognitive impairments and able to read and understand Chinese 21,33 . A pilot study was conducted among 300 residents in Beijing in July 2021 to examine whether the survey was acceptable, well-understood and valid.…”
Section: Study Population 221 Survey Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is inconsistent with the existing studies on the public's preference for COVID-19 vaccines 17,20,22 . One recent piece of research also found that people are more willing to undergo vaccination with fewer injection times 23 . According to the health belief model, in this study, the opposite results may stem from the impact of news reports on people's cognition of vaccination 8 .…”
Section: Discussionmentioning
confidence: 99%